Polymer composites reinforced by nanotubes as scaffolds for tissue engineering - Wang, Wei (2014)
The interest in polymer based composites for tissue engineering applications has been increasing in recent years. Nanotubes materials, including carbon nanotubes (CNTs) and noncarbonic nanotubes, with unique electrical, mechanical, and surface properties, such as high aspect ratio, have long been recognized as effective reinforced materials for enhancing the mechanical properties of polymer matrix. This review paper is an attempt to present a coherent yet concise review on the mechanical and biocompatibility properties of CNTs and noncarbonic nanotubes/polymer composites, such as Boron nitride nanotubes (BNNTs) and Tungsten disulfide nanotubes (WSNTs) reinforced polymer composites which are used as scaffolds for tissue engineering. We also introduced different preparation methods of CNTs/polymer composites, such as in situ polymerization, solution mixing, melt blending, and latex technology, each of them has its own advantages.